Pengaruh Kualitas Layanan Terhadap Tingkat Kepuasan Masyarakat Pada Program Budayakan Arsip Keluarga Menjadi Dokumen Berharga(BASIKAMEH) Di Dinas Perpustakaan Dan Kearsipan Kota Solok Provinsi Sumatera Barat - Endah Fauziah Giska; Jeihan Nabila (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
The purpose of this study is to describe (1) the quality of service in the BASIKAMEH program, (2) the level of community satisfaction in Solok City, (3) the effect of BASIKAMEH program service quality on the level of community satisfaction in Solok City. This research is a quantitative research with descriptive method. This study took 57 respondents who were participants in the BASIKAMEH program. The sampling technique in this study used simple random sampling using the Slovin formula. The data collection techniques used were observation, questionnaires (questionnaires), and also unstructured interviews. The results of this study indicate that the service quality variable gets an average value of 3.19 which is in the "Good" category. So it can be said that the quality of service in the BASIKAMEH program has been good during its implementation. The community satisfaction variable gets an average value of 3.25 which is in the "Very Satisfied" category. So it can be said that community satisfaction with the BASIKAMEH program is very satisfying for the community. Based on the analysis of the questionnaire results, the service quality of the BASIKAMEH program in Solok City, West Sumatra affects community satisfaction in Solok City. This is in accordance with the results of the correlation coefficient of 0.369 which is classified as a weak correlation. The relationship between variables X and Y is positive, this indicates that the higher the quality of service provided, the level of satisfaction will also increase, and vice versa.